Formation Mechanism of Crystal Spots in Jian Kiln Oil-Spot Glaze Revealed by Simulation Experiments - Caishui Jiang; Junming Wu; Jianer Zhou; Ting Luo; Qifu Bao; Kun Liu (Applied Sciences)
The crystalline morphology and glaze color of Jian Kiln oil-spot glaze porcelain exhibit artistic beauty, making it one of the typical representatives of iron-based crystallized black porcelain from the Song Dynasty in China. This study sampled a series of specimens from key temperature points during simulation experiments, employing rapid air quenching to preserve the high-temperature state, capturing the formation process of oil-spot glaze crystals in Jian kiln ceramics. Key samples were subjected to microscopic structure and phase analysis using scanning electron microscopy (SEM), laser Raman spectroscopy (LRS), and X-ray photoelectron spectroscopy (XPS), revealing the formation mechanism of oil-spot glaze crystals in Jian kiln ceramics. The results indicate that the bubbles generated from the decomposition of iron oxide at high temperatures facilitate the migration and enrichment of iron-rich particles towards the glaze surface, laying a crucial material foundation for the subsequent crystallization process. The high-temperature reducing atmosphere accelerates the decomposition reaction of iron oxide, altering the concentration of Fe2+ in the glaze, the viscosity of the melt, and the surface tension, all of which are critical conditions that promote the formation of oil-spot glaze crystals. During the cooling phase, Fe3O4 nanocrystals oxidize into ε-Fe2O3 crystals, with external iron sources migrating inward to support ε-Fe2O3 crystal growth. This process gradually leads to the formation of micrometer-scale, leaf-shaped ε-Fe2O3 crystals that fully occupy the crystalline spots. The coloration of crystalline spots is closely tied to the size of the crystals. Thus, by adjusting the cooling regime, it is possible to create iron-based crystallization glazes with innovative color effects. Furthermore, this study offers significant insights for understanding the crystallization mechanisms of other ancient Chinese high-temperature iron-based crystallization glazes.